Flavours without borders: A cultural and gastronomic exploration of global cuisines, culinary diversity, and fusion experiences in food courts - I Wayan Pugra; I Wayan Basi Arjana; I Ketut Suarja; Ni Wayan Sadiyani; Ratri Paramita; Ni Ketut Sekarti; I Ketut Surata; I Wayan Sunarsa (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
The food court at Jimbaran, Bali, is a vibrant culinary hub offering a diverse array of local and international cuisines. This study explores the culinary experiences within the food court, examining visitor preferences, food variety, and the cultural significance of the dishes. Using a qualitative descriptive method, the research incorporates direct observations, interviews with food vendors and visitors, and thematic analysis of the available culinary options. The findings highlight a unique blend of traditional Balinese cuisine, Indonesian specialties, and international dishes catering to both local and foreign tourists. Popular choices include seafood grills, Balinese lawar, and globally influenced street food-style offerings. Additionally, the study identifies key factors contributing to customer satisfaction, such as food quality, pricing, ambiance, and service. The research concludes that Jimbaran’s food court is more than a dining space—it serves as a cultural attraction reflecting Bali’s dynamic culinary landscape. The fusion of traditional and modern flavours enhances its appeal, making it a must-visit destination for food enthusiasts. Future research could examine the impact of culinary tourism on local businesses and the sustainability of food sourcing in commercial dining spaces.